STRENGTHENING STUDENT CHARACTER THROUGH HORIZONTAL GARDEN PROGRAM AT SMP NEGERI 1 BRINGIN - Umi Khalimatul Dzikriyah; Afifah Rif’atin Nisa; Muhammad Nurul Ihsan Asmawi; Miftahcudin Arjuna; Khoirul Bariyyah (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This article examines the strengthening of the values of cooperation and environmental care through the implementation of the Horizontal Garden Program at SMP Negeri 1 Bringin. This study is motivated by the need for contextual and school-based character education strategies. The research aims to describe the implementation process of the program and analyze its contribution to the development of students’ character. A descriptive qualitative approach was employed, using interviews, observations, and documentation as data collection techniques, supported by interactive data analysis. The findings indicate that the program was carried out through several stages, including planning, socialization, core implementation, and plant maintenance, involving teachers, students, and parents. The program facilitated the emergence of cooperative behavior through group work, task division, and coordination among participants. Meanwhile, environmental care developed through students’ direct experience in nurturing plants, keeping the garden area clean, and initiating ecological actions without being instructed. The discussion highlights that collective involvement and the social capital built throughout the activities effectively reinforced the internalization of character values. The school environment also showed significant improvements, becoming greener, more orderly, and more supportive of character learning. The study concludes that the Horizontal Garden Program is effective as a model of environment-based character education aligned with the Merdeka Curriculum and has the potential to be adopted by other schools.